The Pearl : a true tale of forbidden love in Catherine the Great's Russia - Smith, Douglas, 1962- (Yale University Press, 2008)
Filled with a remarkable cast of characters and set against the backdrop of imperial Russia, this tale of forbidden romance could be the stuff of a great historical novel. But in fact The Pearl tells a true tale, reconstructed in part from archival documents that have lain untouched for centuries. Douglas Smith presents the most complete and accurate account ever written of the illicit love between Count Nicholas Sheremetev (1751-1809), Russia's richest aristocrat, and Praskovia Kovalyova (1768-1803), his serf and the greatest opera diva of her time. Blessed with a beautiful voice, Praskovia began her training in Nicholas's operatic company as a young girl. Like all the members of Nicholas's troupe, Praskovia was one of his own serfs. But unlike the others, she utterly captured her master's heart. The book reconstructs Praskovia's stage career as "The Pearl" and the heartbreaking details of her romance with Nicholas-years of torment before their secret marriage, the outrage of the aristocracy when news of the marriage emerged, Praskovia's death only days after delivering a son, and the unyielding despair that followed Nicholas to the end of his life. Written with grace and style, The Pearl sheds light on the world of the Russian aristocracy, music history, and Russian attitudes toward serfdom. But above all, the book tells a haunting story of love against all odds